The Enrichment of HBV Immune-Escape Mutations during Nucleoside/Nucleotide Analogue Therapy. Issue 8 (November 2017) - Shan, Menglin; Shen, Zhen; Sun, Hua; Zheng, Jianghua; Zhang, Min
Background: Drug-resistant HBV mutants frequently arise during nucleoside/nucleotide analogue (NA) therapy, while the resistance mutations on polymerase also have consequent changes in the S protein. The enrichment of immune-escape mutations was negatively correlated with hepatitis B surface antigen (HBsAg) clearance under NA therapy. This study aims to characterize the variability of HBV polymerase and surface antigen in patients with virological breakthrough under NA therapy. Methods: From 2012 to 2014, serum samples were collected from 156 patients with chronic hepatitis B infection, who had experienced NA therapy for at least 24 weeks and displayed virological breakthrough, while 165 HBV carriers without NA treatment were also enrolled. HBV DNA was quantified and polymerase reverse transcriptase domain was amplified and sequenced. Results: A total of 97 patients in the NA treatment group had resistance mutations, with rtM204I/V/S being the most common substitution (78 of 97), while no resistance mutations were detected in the treatment-naive group. Various escape mutations were detected, and the detection rate was significantly higher in the NA treatment group (38, 24.4%) than that of treatment-naive group (18, 10.9%; P <0.05). Except for the combination of sP120T+sA128V, other double combinations ( n =11) were only detected in the NA treatment group, and nine of these combinations in the treatment group were detected in HBV variants without antiviral resistance mutations. Conclusions: Antiviral resistance mutations were selected by a long duration of NA therapy. Virological breakthrough was not only attributed to the emergence of resistance mutations, but may also be associated with the enrichment of immune-escape mutations.